2020
DOI: 10.3390/metabo10110433
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Permethylated O-Glycans, Free Oligosaccharides, and Glycosphingolipid-Glycans Using Porous Graphitized Carbon (PGC) Column

Abstract: Glycosylation is one of the most common and complex post-translational modifications of proteins. However, there are other carbohydrates such as free oligosaccharides and glycosphingolipids-glycans that are associated with important biological and clinical roles. To analyze these molecules using liquid chromatography coupled with mass spectrometry (LC-MS), the permethylation approach was utilized. Although permethylation is a commonly utilized glycan derivatization technique, separation of permethylated glycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…An early study showed only partial separation of permethylated Man7 and Man8 isomers derived from RNase B ( Stavenhagen et al, 2015 ). Then, Zhou et al, 2017a , b introduced a high temperature PGC-LC-MS method that enables an efficient isomeric separation of both permethylated N-glycans and smaller glycans such as O-glycans, ganglioside glycans, and free oligosaccharide ( Cho et al, 2020 ). With the development of these methods, PGC-LC-MS of isomeric permethylated glycomics has been applied to address many biological issues such as breast cancer ( Peng et al, 2019 ), liver cancer ( Huang et al, 2017b ), colorectal cancer ( Madunić et al, 2021 ), and more ( Huang et al, 2017b ; Xu et al, 2020 ; Zhang et al, 2020b ; Flynn et al, 2021 ).…”
Section: Mass Spectrometry-based Separation Techniques Facilitate Gly...mentioning
confidence: 99%
“…An early study showed only partial separation of permethylated Man7 and Man8 isomers derived from RNase B ( Stavenhagen et al, 2015 ). Then, Zhou et al, 2017a , b introduced a high temperature PGC-LC-MS method that enables an efficient isomeric separation of both permethylated N-glycans and smaller glycans such as O-glycans, ganglioside glycans, and free oligosaccharide ( Cho et al, 2020 ). With the development of these methods, PGC-LC-MS of isomeric permethylated glycomics has been applied to address many biological issues such as breast cancer ( Peng et al, 2019 ), liver cancer ( Huang et al, 2017b ), colorectal cancer ( Madunić et al, 2021 ), and more ( Huang et al, 2017b ; Xu et al, 2020 ; Zhang et al, 2020b ; Flynn et al, 2021 ).…”
Section: Mass Spectrometry-based Separation Techniques Facilitate Gly...mentioning
confidence: 99%
“…Exoglycosidase enzymatic digestion has been utilized to elucidate the glycan and glycopeptide isomers (Cho et al, 2020; Royle et al, 2006). However, this approach is commonly combined with LC‐MS or CE‐MS to separate the digested products from the precursor glycans.…”
Section: Ms‐based Isomeric Characterization Of Glycans and Glycopeptidesmentioning
confidence: 99%
“…Dong et al examined the reduced and permethylated free oligosaccharide isomers derived from human, bovine, and goat milk samples (Dong et al, 2016). Subsequently, PGC‐LC‐MS was utilized to demonstrate the isomeric separation of free reducing end and reduced end O‐ glycans, free oligosaccharides from human milk, and GSL glycans derived from the MDA‐MB‐231BR cancer cell line (Cho et al, 2020).…”
Section: Lc‐ms Analysis Of Permethylated Glycan Isomersmentioning
confidence: 99%
“…Compared to RPLC and HILIC, PGC has higher isomeric separation efficiency due to its retention mechanism. PGC columns have been widely employed as a powerful tool for glycan profiling and isomeric separation studies in native, reduced end, and permethylated glycans [84,93,105,106]. The hydrophobic interaction between the stationary phase and analytes, and the remarkable polar retention effect of graphite, facilitate the isomeric separation.…”
Section: Pgc Separationmentioning
confidence: 99%